Saberes tradicionales sobre el uso de plantas medicinales y otros conocimientos de la comunidad nativa “Peneyta” en el río Putumayo - Calderon Ramirez, Denisse Danae (2024)
This study investigates Traditional Knowledge regarding the use of medicinal plants and other insights within the Native Community "Peneyta" along the Putumayo River, concerning the knowledge held by the local inhabitants. To achieve this objective, qualitative research with a narrative design was conducted, and the collected information was analyzed using descriptive statistics. Data were processed through tools such as Excel and SPSS for organization and analysis. Subsequently, a descriptive analysis was performed to summarize survey data, followed by appropriate inferential tests to assess significant relationships and differences between survey questions. Additionally, a qualitative analysis was conducted to interpret observations about medicinal plants present and used in the native community "Peneyta," describing some features based on the information obtained from the survey. The results demonstrate that in the Peneyta Native Community, residents have knowledge about the use of medicinal plants, as well as cultural syndromes. Likewise, the results showcase various traditional practices and techniques for the collection and preparation of medicinal plants.